Assessment of Coronary Artery Calcification in Chronic Kidney Disease Patients Using Multislice CT Correlation with Serum Phosphate Levels - Muhammad Tayyab, Pardeep Sainani, Nabeela Saeed, Muhammad Irshad Khan, Shoukat Ali, Muhammad Ahmad Raza Butt (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality, largely due to accelerated vascular calcification. Objective: This study aims to assess the burden of CAC using multislice computed tomography (MSCT) and evaluate its correlation with serum phosphate levels in patients with CKD. Methods: This cross-sectional analytical study was conducted at Medicine Department, Pakistan Atomic Energy Commission General Hospital, Islamabad from January 2023 to June 2023. A total of 189 patients diagnosed with chronic kidney disease. Demographic and clinical information, including age, sex, duration of CKD, and comorbidities, were recorded on a predesigned data collection form. Venous blood samples were collected under aseptic precautions to measure serum phosphate levels using standard enzymatic methods. Results: The mean age of patients was 57.8 ± 12.3 years, with 64% being male. CAC was detected in 77.8% of patients, with 22.8% exhibiting severe calcification. A significant positive correlation was observed between serum phosphate levels and Agatston scores (rho = 0.472, p < 0.001). Patients with severe CAC had higher phosphate levels (6.1 ± 1.0 mg/dL) compared to those with no calcification (4.4 ± 0.7 mg/dL, p < 0.001). Dialysis patients showed significantly greater CAC burden and higher phosphate levels than non-dialysis patients (p < 0.01). Phosphate levels also increased progressively with advancing CKD stage (p < 0.001). Conclusion: Coronary artery calcification is highly prevalent in CKD patients and is significantly associated with elevated serum phosphate levels. These findings highlight the importance of early phosphate control and vascular screening, even in non-dialysis CKD patients. Keywords: Chronic kidney disease, coronary artery calcification, serum phosphate, multislice computed tomography.